2019
DOI: 10.4028/www.scientific.net/ddf.391.48
|View full text |Cite
|
Sign up to set email alerts
|

Drying of Industrial Hollow Ceramic Brick: A Numerical Analysis Using CFD

Abstract: The drying process can be defined how unit operation for removing water of one moist solid to an unsaturated gaseous phase due to heat transfer. Numerical simulation emerges like a tool that allows the reproduction of drying experiments using computers and suitable softwares. In this sense, this works aims to predict drying process of an industrial hollow ceramic brick inside the kiln using computational fluid dynamics analysis. For one drying temperature of 60°C, results of the drying and heating kinetics, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In the consulted literature, no studies were found that evaluated the drying process of ceramic materials at low temperatures (less than 50 • C). In addition, such works are limited to simpler geometries, such as hollow bricks and ceramic blocks [1,3,5,7,8,13,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It was also noticed that the only operational parameter evaluated in the drying process of ceramic materials reported in the literature is the temperature of the drying air; parameters not being evaluated, for example, were cases involving the same temperature and different values for relative humidity and/or velocity, including dimensions variations.…”
Section: Introductionmentioning
confidence: 99%
“…In the consulted literature, no studies were found that evaluated the drying process of ceramic materials at low temperatures (less than 50 • C). In addition, such works are limited to simpler geometries, such as hollow bricks and ceramic blocks [1,3,5,7,8,13,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It was also noticed that the only operational parameter evaluated in the drying process of ceramic materials reported in the literature is the temperature of the drying air; parameters not being evaluated, for example, were cases involving the same temperature and different values for relative humidity and/or velocity, including dimensions variations.…”
Section: Introductionmentioning
confidence: 99%
“…In general, several studies related to drying of clay material have been realized by experiments [3][4][5][6] and simulations [7][8][9][10][11][12][13][14][15][16]. For drying predictions, mathematical models based on Fick's and Fourier's laws of diffusion have been frequently used for different materials, considering heat and mass transfer mechanisms, initial moisture content and temperature, volumetric variations, and external environmental conditions [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) simulations have been used with success at different fields, having shown to be a powerful technique in the analysis of different physical and chemical problems. However, research studies involving brick drying using CFD analysis are scarce and, in general, devoted to specific geometries [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Its purpose is to identify better drying conditions (optimized process), with less process time, in order to reduce or eliminate dry material waste, by using a CFD analysis. The authors have contributed to the numerical study of the drying ceramic brick considering the mass and heat transfer and fluid flow in the air around the solid in previous works [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%